2004
DOI: 10.1016/s0095-4470(03)00032-9
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete neutralization and other sub-phonemic durational differences in production and perception: evidence from Dutch

Abstract: Words which are expected to contain the same surface string of segments may, under identical prosodic circumstances, sometimes be realized with slight differences in duration. Some researchers have attributed such effects to differences in the words' underlying forms (incomplete neutralization), while others have suggested orthographic influence and extremely careful speech as the cause. In this paper, we demonstrate such sub-phonemic durational differences in Dutch, a language which some past research has fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
144
1
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(159 citation statements)
references
References 17 publications
(35 reference statements)
10
144
1
4
Order By: Relevance
“…For example, during forced-choice two-alternative identification tasks, speakers of German have shown above-chance-level performance on voicing, with the majority of phonologically voiced but phonetically devoiced segments being attributed to the voiced category (e.g., Port and O'Dell 1985;Port and Crawford 1989;Röttger et al 2011). Comparable results have also been reported for other devoicing languages, including Dutch (e.g., Warner et al 2004) and Polish (e.g., Slowiaczek and Szymanska 1989), as well as for other types of perceptual tasks, such as discrimination experiments (e.g., Matsui 2011) and rating tasks (e.g., Ernestus et al 2007a). This suggests that listeners perceive the partial cues to voicing and interpret them as evidence of the target segment being [þvoiced].…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…For example, during forced-choice two-alternative identification tasks, speakers of German have shown above-chance-level performance on voicing, with the majority of phonologically voiced but phonetically devoiced segments being attributed to the voiced category (e.g., Port and O'Dell 1985;Port and Crawford 1989;Röttger et al 2011). Comparable results have also been reported for other devoicing languages, including Dutch (e.g., Warner et al 2004) and Polish (e.g., Slowiaczek and Szymanska 1989), as well as for other types of perceptual tasks, such as discrimination experiments (e.g., Matsui 2011) and rating tasks (e.g., Ernestus et al 2007a). This suggests that listeners perceive the partial cues to voicing and interpret them as evidence of the target segment being [þvoiced].…”
Section: Introductionsupporting
confidence: 64%
“…At the same time, experimental studies have repeatedly shown that speakers of neutralizing languages maintain acoustic differences between phonologically voiced versus voiceless final obstruents and that listeners can often identify the voicing setting of such segments at an above-chance level (e.g., Port and O'Dell 1985;Warner et al 2004). The current study investigates how such identification responses vary depending on whether the perceptual stimuli were recorded using reading vs. non-reading procedures and with vs. without full minimal pairs in the experimental list.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations